RETENTION FACTORS AFFECTING ARTISANS IN THE HEAVY MOTOR VEHICLE INDUSTRY - White, David (My University, 2012)
The heavy motor vehicle industry in South Africa is reliant on artisans for the maintenance and servicing of vehicles. There is a perceived shortage of skills as the industry has shown significant growth during the past decade. However, a similar increase in the supply of adequately trained artisans has unfortunately not occurred. This perceived shortage, together with changes in the employer/employee relationship has increased the mobility of artisans. The result is increased competition amongst companies as they try to attract and retain the best talent. The purpose of this research has been to determine the key retention factors that artisans consider being the most important. A structured questionnaire was used to conduct the research, and both quantitative and qualitative data was collected. The sample comprised 50 artisans from ten organizations, they represented a wide range of demographic groupings. Content analysis was used to determine the results of the qualitative section, while the quantitative section was analyzed using descriptive statistical techniques. Based on the data collected, the researcher was able to determine the top five push and pull factors affecting the retention of artisans. In addition to these retention factors, the research yielded the top career needs that artisans consider important in their jobs. It was found that the retention factors and career needs differed significantly according to both race and age. An artisan retention model was developed, providing a diagnostic tool for organisations wishing to improve the retention of their artisans
MBA thesis - WBS
Keywords: Retention factors; Heavy motor vehicle industry; Employment